Human papillomavirus type distribution in cervical intraepithelial neoplasia grade 2/3 and cervical cancer in Portugal: a CLEOPATRE II Study - Pista, Angela (2014)
Collaborators (54): Tavares A, Dias M, Rocha E, Telhado Mda C, Afonso A, Loureiro M, Horgan C, Marques I, Cortes E, Alegra S, Serra Mdo C, Lima J, Afonso E, Ladeíra AP, Gonçalves L, Sobral N, Reforço AS, Pacheco MA, Enriquez JL, Lagoa A, Ribeiro V, Ferreira L, Cadilla AJ, Furtado JM, Rodrigues J, de Castro PV, e Silva AA, Mota F, Moura P, da Silva TS, Jardim O, Nascimento M, Dacosta A, Borrego J, Fernandes R, Vitorino A, Paula T, Palma F, Paula M, Fatela A, Sobral D, Pereira P, Grilo I, Ambrosio P, Torrezão I, Biscaia I, Nunes S, Araújo M, Sâncio S, Valente G, Mendonça S, Verdasca N, Oliveira A, Santos S.